Warm Water Foot Soaking Therapy in Improving Ankle Brachial Index (ABI) in Patients with Type 2 Diabetes Mellitus: A Case Study - Dhuma Aza Alwintara; Okti Sri Purwanti (Sarana Ilmu Indonesia (salnesia), 2026)
Type 2 Diabetes Mellitus (DM) could lead to peripheral vascular complications, one of which was Peripheral Arterial Disease (PAD), which could be assessed using the Ankle Brachial Index (ABI). A decrease in ABI increased the risk of diabetic foot ulcers and amputation. The aim of this study was to evaluate changes in ABI values after the intervention of warm water foot soaking therapy in patients with type 2 DM. The study design used a descriptive case study conducted on two patients with type 2 DM. ABI was measured before and after routine warm water foot soaking therapy was administered. Both patients showed an increase in ABI values of 0.2, from the category of moderate circulation impairment to normal, indicating an improvement in peripheral perfusion. Warm water foot soaking therapy was shown to have the potential to increase ABI in patients with type 2 DM as a simple and safe non-pharmacological intervention. Further studies with larger sample sizes are needed to confirm the effectiveness and generalizability of the results.